Management Contracts in Water and Sanitation : Gaza's Experience - Saghir, Jamal; Sherwood, Elizabeth; Macoun, Andrew (World Bank, Washington, DC, 2012)
In 1995, as the interim agreements between the Palestine Liberation Organization and Israel were signed, water and sanitation services in the Gaza Strip were in crisis. In mid-1996 Lyonnaise des Eaux/Khatib and Alami (LEKA) was awarded a four-year water services management contract to help local government service providers and the Palestinian Water Authority improve water service. Since the contract became active, water quality has improved, water losses have fallen, and consumption and revenues have increased. Despite the improved performance, the management contract has illustrated some limitations. Overall, the Gaza experience suggests that management contracts are most likely to work under four conditions: 1) The primary objective is to rapidly enhance the technical capacity and efficiency of services. 2) Government faces obstacles to committing to a long-term arrangement for private participation in infrastructure or to inducing the private sector to undertake capital investment or take on commercial or political risk. 3) Tariffs are too low to support a long-term arrangement for private participation in infrastructure. 4) Government faces difficulties in securing agreements to allow the long-term involvement of the private sector or the regulatory framework is incompatible with a long-term arrangement for private participation in infrastructure.